A "New" Phenomenon of Chinese Cinema: Happy-New-Year Comic Movie. Issue 1 (1st March 2002) - Ying, Xu; Zhongquan, Xu
The history of Chinese Happy-New-Year comic movie is not long, less than five years, in fact. When the Chinese film industry was reformed from a planned economy to a market economy in 1995, and the National Film Import and Export Company was no longer in charge of domestic film release, most film studios had to find their own way to make money. Filmmakers have had to think of the film market first before they make films. Some have tried to follow Hong Kong to make martial art action movies, others have followed Hollywood to make money-making commercial movies. Under that situation in 1997, the Happy-New-Year comic movie emerged, in the process, shining a spotlight on the base of old Chinese comic films.